Automated Software Testing with Python - Salvatierra, Jose (Packt Publishing, 2019)
Learn about automated software testing with Python, BDD, Selenium WebDriver, and Postman, focusing on web applications About This Video Learn automated software testing with Python Learn to write complete system tests using Python and tools such as Postman In Detail Welcome to the most comprehensive course on automated software testing with Python. Software testing is an essential skill for any developer, and this course will help you truly understand all types of test automation with Python. The focus of this course is on testing for the web-we'll be working with REST APIs and web applications, and technologies such as unittest, Postman, and Selenium WebDriver-ranging from operations such as mocking and patching using the unit test library (to reduce dependencies and turn complex tests into simple ones) to looking at all types of testing: simple unit tests to large system tests and even customer acceptance tests. Throughout the course we work on the Testing Pyramid concept, making sure that we have full coverage of every system component with unit tests. Then we test dependencies using integration tests. Finally, we cover the entire system using system tests. Of course, we also look at what acceptance testing is, how we come up with acceptance tests, and some of the best ways to write acceptance tests for a web application using Behavior-Driven Development and Selenium WebDriver. We also learn about implicit and explicit waits with Selenium WebDriver and Python, a key concept used to speed up the runtime of your acceptance tests. By implementing a Continuous Integration pipeline that runs your tests whenever you make any changes, you'll have much higher project quality so that you don't miss any annoying bugs. We'll look at putting our projects into GitHub and linking with them.